Cadmium-induced impairment in growth, photosynthetic apparatus and redox regulation in green amaranth (Amaranthus viridis L.) plant attenuated by salicylic acid and methyl jasmonate - Md. Tanveer Hussain; Md. Sabibul Haque; Md. Fazle Rabbi; Hafsa Tasnim; Md. Asiful Haque; Arnab Saha; AKM Golam Sarwar; Md. Nesar Uddin; Md. Alamgir Hossain (PLoS ONE, 2025)
The hazardous Cadmium (Cd) contamination in vegetables from anthropogenic Cd-abundant agroecosystems is a decisive threat to plants and human health. This study examined the prospective roles of salicylic acid (SA) and methyl jasmonate (MeJA) in alleviating Cd-induced toxic effects in green amaranth plants. The seeds of green amaranth (cv. Ghretokanchan) plant were primed with SA (100 and 250 µM) and MeJA (2.5 and 5 µM) and 21-d-old seedlings were set in six conditions under a hydroponic system: (i) Control, (ii) Cd (10 µM CdCl2·H2O), (iii) Cd with 100 µM SA, (iv) Cd with 250 µM SA, (v) Cd with 2.5 µM MeJA, and (vi) Cd with 5.0 µM MeJA. The experiment was set in a completely randomized design having three replications. Cd exposure for three weeks markedly impaired plant growth, pigment contents, leaf gas exchange, and photosystem-II efficiency; increased malondialdehyde (MDA) and hydrogen peroxide (H2O2) levels indicating induced oxidative stress; and enhanced the activities of superoxide dismutase, guaiacol peroxidase and catalase enzymes. However, seed priming and supplementation of SA and MeJA significantly remediated these Cd-mediated adverse effects. Compared to Cd-alone treatment, 100 and 5 µM of SA and MeJA considerably improved total dry weight by 45% and 94%, respectively whereas leaf MDA and H2O2 levels were substantially reduced by 100 µM SA (37% and 14%) and 5 µM MeJA (35% and 21%). An extensive activity of antioxidants and considerable reduction in Cd uptake and translocation from medium-root-shoot was apparent due to the supplementation of SA and MeJA. The study effectively optimized the levels of SA and MeJA for the improvement of Cd tolerance based on metal uptake, morpho-physiology, and redox regulation, and concludes that either 100 µM SA or 5 µM MeJA could be used for the alleviation of Cd-toxicity in green amaranth plants in Cd-contaminated soils through further field trials.